Wild souls : freedom and flourishing in the non-human world - Marris, Emma (Bloomsbury Publishing, 2021)
"From an acclaimed environmental writer, a groundbreaking and provocative new vision for our relationships with--and responsibilities toward--the planet's wild animals"--